Land‐Use Impacts on Plant Functional Diversity Throughout Europe - Francesca Rosa; Peter M. van Bodegom; Stefanie Hellweg; Stephan Pfister; Idoia Biurrun; Steffen Boch; Milan Chytrý; Renata Ćušterevska; Michele Dalle Fratte; Gabriella Damasceno; Emmanuel Garbolino; Jonathan Lenoir; et al. (Global Ecology and Biogeography, 2025)
Aim Global biodiversity loss resulting from anthropogenic land‐use activities is a pressing concern, requiring precise assessments of impacts at large spatial extents. Existing models mainly focus on species richness and abundance, lacking insights into ecological mechanisms and species' roles in ecosystem functioning. To bridge this gap, we conducted an extensive analysis of the impact of human land use on vascular plant functional diversity across diverse land‐use classes and bioregions in Europe, comparing it to traditional metrics. Location Europe. Time Period 1992–2019. Major Taxa Studied Vascular plants. Methods Integrating extensive databases of vegetation plots with spatial data on land use and land cover, we paired plots from areas actively used and modified by humans with plots from natural habitats under similar environmental conditions. Using species occurrences and traits, in each plot we computed three complementary functional diversity metrics (functional richness, evenness and divergence), species richness and abundance. We assessed the impact of land use by comparing the metrics in the paired plots. Results Our findings revealed that, compared to natural habitats, anthropogenic land use exhibits lower functional richness and divergence but higher functional evenness across most land‐use classes and bioregions. The response of functional richness was more marked than the other two metrics and especially pronounced in croplands and urban areas and in northern bioregions. Functional richness exhibited a pattern that did not fully overlap with the trend in species richness, providing useful complementary information. Main Conclusions We provide a large‐scale precise assessment of anthropogenic land‐use impacts on functional diversity across Europe. Our findings indicate that: (i) human disturbance significantly alters plant functional diversity compared to natural habitats; (ii) this alteration goes in the direction of functional homogenisation within sites; (iii) functional diversity metrics complement traditional metrics by offering deeper insights into the ecological mechanisms in response to anthropogenic land use.